2001
DOI: 10.1080/028418601750288181
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Male Breast Cancer—A Case-Control Study from Scandinavia

Abstract: We report a population-based case-control study on risk factors for male breast cancer. Data on a broad range of previously suggested risk factors were collected in a set of Scandinavian breast cancer cases and matched controls. Incident cases (n = 282) with histologically verified carcinomas of the breast were identified from notification to the cancer registries of Denmark, Norway and Sweden over a 4-year period 1987-1991 and of these cases, 156 men could be approached and responded. Controls were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
4
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 12 publications
1
80
4
15
Order By: Relevance
“…These rates are not different from those of the normal population (18). A positive family history increases the relative risk 2.5 times, and 20% of men with breast cancer have a first degree relative with the same disease (4,19). While the relative risk for a first second male breast cancers 30 times higher, this rate is only around 2-4 times for women.…”
mentioning
confidence: 84%
“…These rates are not different from those of the normal population (18). A positive family history increases the relative risk 2.5 times, and 20% of men with breast cancer have a first degree relative with the same disease (4,19). While the relative risk for a first second male breast cancers 30 times higher, this rate is only around 2-4 times for women.…”
mentioning
confidence: 84%
“…Although one small study reported that excessive alcohol consumption was linked to MBC (37), other studies have failed to demonstrate the same (29,38,39). The link between smoking and MBC has also not been clearly demonstrated (29,40). Others have investigated level of exercise and physical activity as a risk factor, but again, no clear association has been established (29,40,41).…”
Section: Risk Factors For Mbcmentioning
confidence: 99%
“…The link between smoking and MBC has also not been clearly demonstrated (29,40). Others have investigated level of exercise and physical activity as a risk factor, but again, no clear association has been established (29,40,41). Risk factors for MBC are summarized in Table I.…”
Section: Risk Factors For Mbcmentioning
confidence: 99%
“…Exposures of humans as well as rodents suggest that DEHP induces cancer through multiple molecular signals, including DNA damage [145]. It has been implicated in the development of male breast cancer and may cause reproductive problems among both men and women who work in PVC fabricating operations [146,147]. Elevated breast cancer risk among women in phthalate-exposed population in northern Mexico was reported by López-Carrillo et al [148].…”
Section: Phthalatesmentioning
confidence: 97%